8B.001 Bush Nippers: Feasibility of an inland lifesaving pilot program for Victorian children. (14th March 2021) - Strugnell, Grace; Birch, Rhiannon; Micallef, Trudy; Simpson, Kate; Matthews, Bernadette
Abstract : Background: In 2018–19, residents in regional Victoria, Australia were almost twice as likely to drown compared to those in metropolitan Melbourne. 'Nippers' programs provide lifesaving and water safety knowledge and skills to children aged 5–14 years in coastal locations. However, a 49% increase in inland waterway drowning compared with the 10-year average, highlights the need to provide a similar program to children in inland regions. Aim: To determine the feasibility of the Bush Nippers pilot program in inland regions. Methods: The existing Nippers program was adapted for inland settings. Three programs delivered content at river and/or pool locations. Evaluation included two age groups; with skills assessed by program instructors, and independent researchers conducting pre-post program quizzes, and parent and instructor surveys. Results: This study is nearing completion; with final results presented at the conference. Preliminary results indicate over 400 children participated in Bush Nippers. Participants' lifesaving and water safety knowledge increased 11% (Under 9, n=26) and 7% (Under 12, n=23); and they attained skills, particularly rescues, survival swimming, lifejackets and rescue boards. Parents (100%, n=49) and instructors (89%, n=9) would recommend the program and parents (92%) thought their child would participate again. Conclusion and Learning Outcomes: Given the high regard and demand for the program, and importance of lifesaving skills, provision of a scalable lifesaving program in inland regions may address the drowning trend and improve aquatic participation. State-wide adoption by schools and other providers is possible. Content, delivery and training should be location-specific, flexible and economically sustainable.